Teacher Education and Insertion of LIBRAS (Brazilian Sign Language) in Higher Education: Current Perspectives - Mosca Giroto, Claudia Regina [UNESP]; Sartoreto de oliveira Martins, Sandra Eli [UNESP]; Rodrigues de Lima, Jessica Mariane [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
The Brazilian law n. 10.436/2002 (BRASIL, 2002), regulated by the decree n. 5.626/2005 (BRASIL, 2005), provides the insertion of the discipline of LIBRAS (Brazilian Sign Language), on a mandatory basis in Pedagogy, Speech Therapy and other teaching degrees in Higher Education. Based on this legislation, this research, associated with the CAPES' Observatory Program of Education, linked to the network project Accessible Higher Education, aimed to investigate the introduction of this discipline in the curriculum of Pedagogy, Speech Therapy and other teaching degrees in public universities. It also questions the purpose of this discipline in these courses, compared to provisions described in the 2005 decree. We obtained curriculum and lesson plans available in the public domain format and/or forwarded by the coordinator of the courses in question, and the analysis of these documents included the categories: Courses that offer the Libras discipline - divided into Mandatory and Optional disciplines - and Courses that do not offer the Libras discipline. Regarding the lesson plans of the elected categories, we highlight Proposals of the discipline' and Content addressed. According to the results, only four courses offer such disciplines. Other 42 courses do not meet the 2005 decree, a fact that led to the conclusion that obedience to the related regulations has not received the necessary attention in the training of teachers and speech therapists at the university investigated.
Keywords: Deafness; Teacher Education; Brazilian Sign Language (LIBRAS); Higher Education; Educational Policies